Lipid Delivery System and Functional Food - Deng, Qianchun; Liu, Ruijie; Xu, Xin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The articles collected focused on the construction of delivery systems aiming at enhancing the physicochemical stability, bioavailability, and bioactivity of active lipids and liposoluble ingredients, as well as flavor retention and slow release, and its potential application in the development of functional foods with different phase states and suitable for the physiopathological characteristics of different populations. A growing application of lipids and liposoluble ingredients are emerging in functional foods, such as beverages, meal replacement powders, and foods with special medical purpose. Liposoluble ingredients including polyunsaturated fatty acids (PUFA), phytosterols (esters), carotenoids, polyphenols, and liposoluble vitamins, play an important role in balancing the insufficient nutrient intake and occurrence of chronic diseases. However, a critical challenge for their efficient and rational application arises due to the properties of strong hydrophobicity, easy oxidation, unpleasant flavor, and adverse interaction with other components. The construction, perfection, and regulation of lipid delivery system are of great significance for overcoming the challenge.